A multi-objective optimization approach for sustainable water management for places with over-exploited water resources. (2nd February 2019) - Pérez-Uresti, Salvador I.; Ponce-Ortega, José María; Jiménez-Gutiérrez, Arturo
Highlights: Several places around the world face water scarcity. Rainwater harvesting can be consider as a valuable source of water. An optimization mode that includes the use of rainwater harvesting for the design of water networks is presented. The model is applied to the city of Queretaro, Mexico. It is shown how the use of rainwater harvesting can help to the recovery of deep wells under depletion. Abstract: Rainwater harvesting (RWH) is analyzed in this work as an option for water supply for places with over-exploited water resources. The model is formulated under a multi-period, multi-objective optimization model. The objective is two fold, first to assess the potential of RWH as an alternative water source, and second to design an optimal water distribution network in which both natural and alternative sources work as an integrated system. The problem is formulated to account for three different objectives, namely maximum profit, minimum groundwater usage and minimum investment cost. A case study for the city of Queretaro in Mexico was considered to show the applicability of the proposed approach. The results show that as much as 27% of the domestic demand in Queretaro City could be supplied by RWH, which would lead to a significant recovery of deep wells currently under depletion.